Physics-informed Priors Improve Gravitational-wave Constraints on Neutron-star Matter - Spencer J. Magnall; Christian Ecker; Luciano Rezzolla; Paul D. Lasky; Simon R. Goode (The Astrophysical Journal Letters)
Gravitational-wave astronomy shows great promise in determining nuclear physics in a regime not accessible to terrestrial experiments. We introduce physics-informed priors constrained by nuclear theory and perturbative quantum chromodynamics calculations, as well as astrophysical measurements of neutron-star masses and radii. When these priors are used in gravitational-wave astrophysical inference, we show a significant improvement on nuclear-matter constraints. Applying these to the first observed gravitational-wave binary neutron-star merger GW170817, the constraints on the radius of a 1.4 M _⊙ neutron star improve from ${R}_{1.4}=12.5{4}_{-1.54}^{+1.05}$ to ${R}_{1.4}=12.1{1}_{-1.11}^{+0.91}\,{\rm{km}}$ and those on the tidal deformability from ${\tilde{{\rm{Λ }}}}_{1.186}\lt 720$ to ${\tilde{{\rm{Λ }}}}_{1.186}=38{4}_{-158}^{+306}$ (90% confidence intervals and 95% upper limit) at the source-frame chirp mass ${ \mathcal M }=1.186\,M_{\odot }$ when compared to the LIGO–Virgo–KAGRA analysis with uniform priors. We also show that these priors can be used to perform model selection between binary neutron star and neutron star–black hole mergers; in the case of GW190425, the results provide only marginal evidence with a Bayes factor ${ \mathcal B }{ \mathcal F }=1.33$ in favor of the binary neutron star merger hypothesis. Given their ability to improve the astrophysical inference of binary mergers involving neutron stars, we advocate for these physics-informed priors to be used as standard in the literature and provide open-source code for reproducibility and adaptation of the method.